Independent Curriculum Based Learning Management in Primary School Education Units - Lisdawati, Lisdawati (PPSDP International Journal of Education, 2024)
Implementation of Independent Curriculum-based Learning is a challenge for elementary school teachers to improve the quality of learning processes and outcomes. Therefore, the implementation of an independent curriculum must be supported by competent teachers, effective and efficient learning management, and adequate infrastructure. This research aims to analyze independent curriculum-based learning management in elementary school education units. Data collection tools use interviews, documentation, and literature review. Implementation of the Independent Curriculum in the learning process must be able to build strong awareness and understanding of the Independent Curriculum, design learning plans that reflect the principles of the Independent Curriculum, create a learning environment that supports the Independent Curriculum, encourage active participation of students by always innovating, and be able to involve parents and community in implementing the independent learning curriculum in the learning process. The obstacles faced by teachers such as limited school infrastructure and teacher adaptation and centralization of the curriculum can be followed up by participating in training and professional development to increase understanding of the concepts and principles of the Independent Learning Curriculum.